2012
DOI: 10.1002/zaac.201200138
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Series of [RE2Ca(OQ)8] Structures: New Heterobimetallic Rare Earth/Alkaline Earth 8‐Quinolinolate Complexes

Abstract: A series of heterobimetallic complexes [RE 2 Ca(OQ) 8 ]·nHOQ (RE = Sm, Gd, Tb, Ho, Tm, Yb, Lu, Y, Sc) and the isostructural [Gd 2 Mg(OQ) 8 ] were synthesised and structurally characterised. They were mainly obtained after direct reactions of the elemental rare earth metals with calcium metal in the presence of 8-hydroxyquinoline (HOQ) and a 1,3,5-tri-tert-butyl-benzene (tBuB) flux, and some complexes were synthesised by pseudo solid-state rearrangement reactions between powdered RE(OQ) 3 and AE(OQ) 2 (AE = Mg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The synthesis of quinolinolate complexes containing rare-earths complexes at elevated temperatures (>200 °C) has previously been reported. Initially, using this method, the amorphous precursor material, [Ln(OQ) 3 ] n , is isolated from the aqueous reaction of NaOQ with LnCl 3 to produce a noncrystalline material with a confirmed empirical composition of [Ln(OQ) 3 ] but an unknown speciation (Scheme ). It has now been found that the sparingly soluble material can be sufficiently dissolved in hot acetone by Soxhlet extraction over the course of several days to yield a pure, microcrystalline material of the form [Ln 3 (OQ) 9 ] (Ln = Dy, Gd, Tb).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of quinolinolate complexes containing rare-earths complexes at elevated temperatures (>200 °C) has previously been reported. Initially, using this method, the amorphous precursor material, [Ln(OQ) 3 ] n , is isolated from the aqueous reaction of NaOQ with LnCl 3 to produce a noncrystalline material with a confirmed empirical composition of [Ln(OQ) 3 ] but an unknown speciation (Scheme ). It has now been found that the sparingly soluble material can be sufficiently dissolved in hot acetone by Soxhlet extraction over the course of several days to yield a pure, microcrystalline material of the form [Ln 3 (OQ) 9 ] (Ln = Dy, Gd, Tb).…”
Section: Resultsmentioning
confidence: 99%
“…Our recent work has explored the coordination chemistry and reactivity of 8-hydroxyquinoline (or 8-quinolinol, HOQ). The 8-quinolinolate anions (OQ – ) and related species, such as 2-methyl-8-hydroxyquinolinolate (MQ), are primarily known for their use as strong chelating agents in laboratory-based metal analysis, within organic light-emitting diodes (as aluminum complexes) and as therapeutic reagents for metal chelation. We have reported the use of high-temperature syntheses to isolate a number of alkali-metal, transition-metal, and rare-earth (mainly heterobimetallic) complexes of both the OQ and MQ anions as well as a number of heterometallic species. These complexes are made either by direct reaction of the elemental metal(s) with HOQ or by isolation of the M(OQ) n compound(s) with subsequent high-temperature rearrangement reactions. The homometallic rare-earth quinolinolate precursors are initially isolated as amorphous compounds, and only three examples have been structurally characterized; [Er 3 (OQ) 9 ]·MeCN was obtained from acetonitrile, [Ho 3 (OQ) 9 ]·HOQ formed from an elevated temperature synthesis with holmium and strontium metals, and [Sc 2 (OQ) 6 ] was prepared from [Sc(N(SiMe 3 ) 2 ) 3 ] and HOQ …”
Section: Introductionmentioning
confidence: 99%
“…Heterobimetallic terbium/alkaline earth (Tb/AE) compounds reported in the literature contain either oxygen donors or multifunctional donors, [16] such as [Tb 2 Ca(OQ)8] • nHOQ (OQ = 8quinolate). [17] Fewer examples are known for the bimetallic system Tb/Sr, e. g. [Tb 2 Sr 3 (pda) 6 (H 2 O) 18 ] • 13H 2 O. [18] Previously, the ligand 3-(2-pyridyl)pyrazole (2-PyPzH) was mainly used in the synthesis of transition-metal complexes and CPs, either as the main reacting ligand [19] or as a co-ligand, [20] such as the formation of 2D open-channel cadmium(II) frame-works using the mixed ligands terephthalic acid and 2-PyPzH.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Furthermore, they have attracted interest in use for preparing coordination complexes since the report of tris-8-oxoquinolinato aluminium in 1987, 18,19 and more recently for generating polymetallic lanthanide complexes. [20][21][22][23][24][25][26] We have recently used this pro-ligand to assemble a series of asymmetric lanthanide dimetallics to study the magnetic interactions by magnetometry, electron paramagnetic resonance (EPR) and inelastic neutron scattering (INS) spectroscopies. 27,28 We found that the exchange interactions for the asymmetric Dy 2 and Er 2 species are reasonably well described by the point-dipole model, however, there is a non-negligible superexchange component.…”
Section: Introductionmentioning
confidence: 99%